1977
DOI: 10.1093/jn/107.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Rat Liver Glutathione: Possible Role as a Reservoir of Cysteine

Abstract: Rat liver contains a high concentration (7-8mM) of reduced glutathione and its level changes rapidly when starving or feeding rats. We concluded that one of the functions of liver glutathione was to act as a reservoir of cysteine. When starved rats were fed a protein-free diet, the increase in liver glutathione was dependent on the amount of cysteine added to the diet. A cysteine-dependent increase of glutathione was also observed in rats fed a diet containing gelatin with cysteine, but the increase was relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0
2

Year Published

1984
1984
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(72 citation statements)
references
References 32 publications
2
67
0
2
Order By: Relevance
“…GSH is a non-toxic cysteine storage form with 10 -100 times higher concentrations in mammalian tissues than cysteine (17). Approximately one-third to one-half of the total liver GSH serves as a cysteine reservoir that can be released, when necessary (27).…”
Section: Gsh Functionsmentioning
confidence: 99%
“…GSH is a non-toxic cysteine storage form with 10 -100 times higher concentrations in mammalian tissues than cysteine (17). Approximately one-third to one-half of the total liver GSH serves as a cysteine reservoir that can be released, when necessary (27).…”
Section: Gsh Functionsmentioning
confidence: 99%
“…In the present study, we first investigated the impact of oral administration of L-cystine and L-theanine on the plasma cystine and glutamic acid concentrations. Then, changes in the hepatic GSH levels after antigenic stimulation were analyzed in mice given L-cystine and/or L-theanine orally, as the liver is known to contain high concentrations of GSH that decrease on stimulation with LPS [3,28]. The relative levels of interferon-γ (IFN-γ) and interleukin-10 (IL-10) are believed to be important in determining the balance between T helper (Th) 1/Th2 cells, which in turn determines the direction of activation of cell-mediated immunity or humoral immune response [16,23].…”
mentioning
confidence: 99%
“…It has been reported that the level of GSH decreases in vitamin C-deficient guinea pigs (13). The GSH level in an animal body is strongly dependent on food intake (14). In this experiment the actual amount of feed consumed by animals in group D gradually decreased.…”
Section: Discussionmentioning
confidence: 73%